PENGARUH CAPITAL STRUCTURE, TANGIBLE ASSETS, INTANGIBLE ASSETS, DAN SALES GROWTH TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Properties dan Real Estate Yang Terdaftar di Bursa Efek Indonesia) - Ananda Mira Febriana, Ananda; Triyono , Triyono (Media Mahardhika, 2024)
Company value is very important because it reflects financial performance which can influence investors' assessments. Investors really need stock assessments when deciding to invest. Financial performance is an effort that can be made by each company to measure and predict the success achieved by the company when making a profit. This research examines the influence of capital structure, tangible assets, intangible assets, and sales growth on company value with financial performance as an intervening variable. The population in this study are companies listed on the Indonesia Stock Exchange in 2020-2022. The sample in this research is Properties and Real Estate Companies listed on the Indonesia Stock Exchange in 2020-2022. Based on the purposive sampling method, 156 samples were obtained that met the specified criteria. The type of data used is secondary data. The hypothesis in this study was tested using the latent variable correlation test. Based on the results of the latent variable correlation test, this research concludes that intangible assets have an effect on financial performance; intangible assets influence company value; and financial performance influences company value.